On the detection of supermassive primordial stars – II. Blue supergiants. Issue 3 (15th July 2019) - Surace, Marco; Zackrisson, Erik; Whalen, Daniel J; Hartwig, Tilman; Glover, S C O; Woods, Tyrone E; Heger, Alexander; Glover, S C O
ABSTRACT: Supermassive primordial stars in hot, atomically cooling haloes at z  ∼ 15–20 may have given birth to the first quasars in the Universe. Most simulations of these rapidly accreting stars suggest that they are red, cool hypergiants, but more recent models indicate that some may have been bluer and hotter, with surface temperatures of 20 000–40 000 K. These stars have spectral features that are quite distinct from those of cooler stars and may have different detection limits in the near-infrared today. Here, we present spectra and AB magnitudes for hot, blue supermassive primordial stars calculated with the tlusty and cloudy codes. We find that photometric detections of these stars by the James Webb Space Telescope will be limited to z  ≲ 10–12, lower redshifts than those at which red stars can be found, because of quenching by their accretion envelopes. With moderate gravitational lensing, Euclid and the Wide-Field Infrared Space Telescope could detect blue supermassive stars out to similar redshifts in wide-field surveys.